S37 The persistence of eosinophilic inflammation in copd over time – aeris cohort. (15th November 2016) - Kim, VL; Williams, NP; Ostridge, KK; Naghibi, MM; Coombs, NA; Devaster, JM; Aris, E; Clarke, SC; Tuck, AC; Wootton, SA; Bourne, SC; Staples, KJ; et al.
Abstract : Introduction: The importance of eosinophilic inflammation in COPD is in its ability to predict an enhanced response to treatment, such as corticosteroids. However, little is know about the persistence of higher eosinophils, or its associations with infectious aetiology during clinical stability and exacerbation. We investigated the natural history of eosinophilic inflammation over time and studied eosinophil-associated acute exacerbations of COPD and the impact of seasonality in a cohort of COPD patients. Methods: 127 subjects with moderate to very severe COPD were enrolled into the AERIS cohort (NCT01360398 ) and were reviewed monthly for scheduled visits and during exacerbations. Blood sampling was performed quarterly and at exacerbations. Higher blood eosinophils (BE) were defined as ≥2%. Based on frequency of higher BE over the study, subjects were divided into predominantly (PE), intermittent (IE) and rarely eosinophilic (RE) groups. Results: Blood eosinophil levels ≥2% were prevalent at baseline (68.3%) and at exacerbations (51.1%). Over the study 57.6% of subjects had predominantly, 16.16% intermittently and 26.26% rarely ≥2% blood eosinophils. Higher BE at enrolment was strongly associated with a predominantly high BE profile for the year (AUC 0.841 p < 0.001) and with greater odds of ≥2% eosinophils at exacerbation (OR 9.60 p < 0.001). The odds of ≥2% BE at exacerbation were higher in the PE group compared to the rarely group (OR 12.00, p < 0.001). A larger proportion of exacerbations were eosinophilic in the Summer than Winter (OR 2.57, p = 0.001). The odds of bacterial presence at exacerbation was higher in Winter than Summer among those in the PE group (OR 4.74, CI: 1.43; 15.71, p = 0.011), but not among those in the RE group (OR 1.15, CI: 0.29; 4.56, p = 0.838). Conclusion: Our data suggests that it is possible to stratify COPD patients by stable state blood eosinophil levels. This measure is easily accessible and provides important insights into the longitudinal inflammatory phenotype of COPD. Persistent higher blood eosinophil levels were associated with risk of bacterial infection at exacerbation, and seasonality of exacerbation. Intervention studies are required to establish clear treatment algorithms utilising this measure to stratify therapy.